Penanaman Karakter Positif Pelajar Melalui Pembahasan Fenomena-Fenomena Fisika dan Pendekatan Analogi (Hasil Kajian Perkulihan Fisika Dasar) - Joni Rokhmat (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
The discussion results of Fundamental Physics I lecturing, especially the 1st Newton law about movement, law of Lenz, electromagnetic induction, and law of Bernoulli about pressure of flowing fluid show that in the concepts implicitly there is an action-reaction relation between objects. We could analogize these phenomena to the interaction between human being, in the contex of learning we can analogize it to the interaction between educator and students. When the interaction between objects softly occurs (Ã¢â¬ÅpersuasiveÃ¢â¬Â) the reaction is not emerge but when it happen quictly the reaction emerges and it against the change caused by the action. The implementation of the discussion of Physics concept and analogy approach usefull to implant positive characters to the students. The positive characters include honesty, responsibility, respect, empaty, self restraint, modesty, patient, no despondently, diligent, love, and good samaritan, also make the values to be a habit in the mind, feeling, and in action.